2019
DOI: 10.2135/cropsci2019.02.0101
|View full text |Cite
|
Sign up to set email alerts
|

Genomic‐Wide Association Study of Popping Expansion in Tropical Popcorn and Field Corn Germplasm

Abstract: Popcorn is a popular snack food with higher grain value compared with “field corn” maize (Zea mays L.). In general, popcorn germplasm is less improved than common maize cultivars, with less favorable agronomic performance and greater susceptibility to pests, diseases, and lodging, especially in tropical environments. One approach to expanding and improving popcorn germplasm is to introduce favorable alleles for agronomic performance from field corn. If markers tagging quantitative trait loci (QTLs) associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 73 publications
3
20
0
Order By: Relevance
“…These findings agree with a previous study by Kaur and Kaur (2013), who reported that the hierarchical algorithm provides better results and higher quality than KM. Additionally, the results of this study were consistent with the findings of previous research, indicating that dent corn and popcorn lines from Brazilian germplasms are grouped into two genetically differentiated clusters (Coan et al, 2018;Camacho et al, 2019;Maldonado et al, 2019;Senhorinho et al, 2019). In this regard, the results of this study showed that the DeepAEbased data preprocessing had better accuracy values than those achieved by PCA.…”
Section: Discussionsupporting
confidence: 91%
“…These findings agree with a previous study by Kaur and Kaur (2013), who reported that the hierarchical algorithm provides better results and higher quality than KM. Additionally, the results of this study were consistent with the findings of previous research, indicating that dent corn and popcorn lines from Brazilian germplasms are grouped into two genetically differentiated clusters (Coan et al, 2018;Camacho et al, 2019;Maldonado et al, 2019;Senhorinho et al, 2019). In this regard, the results of this study showed that the DeepAEbased data preprocessing had better accuracy values than those achieved by PCA.…”
Section: Discussionsupporting
confidence: 91%
“…While selecting for a QPMlike proteome, key popcorn traits such as popability, kernel morphology, and kernel size were also selected throughout the breeding program (Ren et al, 2018). Recent studies have observed that popping expansion is controlled by additive genetic factors with significant associations between multiple SNPs and elevated expansion volume (Mafra et al, 2018;Coan et al, 2019;de Lima et al, 2019;Senhorinho et al, 2019). These QTLs may be useful in future studies after associations have been validated independently, but at this stage phenotypic evaluation was determined most effective for selecting quality popcorn traits such as popability and expansion volume.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, genotype-phenotype studies for quantitative traits at the genome level usually require high-density genetic marker panels, i.e., a large number of markers throughout the genome and large population sizes to obtain sufficient power and prediction resolution [1,2]. The development of several genotyping platforms through high-density single nucleotide polymorphism (SNP) arrays, such as genotyping-by-sequencing (GBS) or SNP chips, has enabled the identification of quantitative trait loci (QTL) for different target traits in various plant species [3][4][5][6]. Silva-Junior et al [7], for instance, developed a genome-wide SNP chip for multiple species of Eucalyptus, which has been effective for genomic studies in a wide variety of economically important eucalypt species and their hybrids, including Eucalyptus grandis, Eucalyptus urophylla, Eucalyptus nitens and Eucalyptus globulus [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%